2019
DOI: 10.1074/jbc.ra118.007291
|View full text |Cite
|
Sign up to set email alerts
|

The ORMDL/Orm–serine palmitoyltransferase (SPT) complex is directly regulated by ceramide: Reconstitution of SPT regulation in isolated membranes

Abstract: Edited by George M. CarmanSphingolipids compose a lipid family critical for membrane structure as well as intra-and intercellular signaling. De novo sphingolipid biosynthesis is initiated by the enzyme serine palmitoyltransferase (SPT), which resides in the endoplasmic reticulum (ER) membrane. In both yeast and mammalian species, SPT activity is homeostatically regulated through small ER membrane proteins, the Orms in yeast and the ORMDLs in mammalian cells. These proteins form stable complexes with SPT. In ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 39 publications
8
94
0
Order By: Relevance
“…1B). A recent paper demonstrated that ceramides directly inhibited serine palmitoyltransferase in an ORMDL-dependent manner [47]. We also previously observed that disruption of CERT caused some suppression of de novo sphingolipid biosynthesis including glycolipids in CHO cells [12].…”
Section: Discussionmentioning
confidence: 66%
“…1B). A recent paper demonstrated that ceramides directly inhibited serine palmitoyltransferase in an ORMDL-dependent manner [47]. We also previously observed that disruption of CERT caused some suppression of de novo sphingolipid biosynthesis including glycolipids in CHO cells [12].…”
Section: Discussionmentioning
confidence: 66%
“…The ORMDLs are homeostatic regulators of SPT, inhibiting activity of this enzyme as cellular sphingolipids rise (reviewed in (17)). The ORMDL/SPT complex responds directly to levels of ceramide (65). There are three ORMDL isoforms.…”
Section: Time and Sphingolipid-dependent Changes In Molecular Speciesmentioning
confidence: 99%
“…ORMDL3 inhibits serine-palmitoyltransferase (SPT), the rate-limiting enzyme complex of de novo sphingolipid synthesis (Supplemental Figure 1; supplemental material available online with this article; https://doi.org/10.1172/JCI130860DS1) (8)(9)(10). Sphingolipids are essential building blocks of cellular membranes and constitute key cellular signaling mediators (11).…”
Section: Introductionmentioning
confidence: 99%
“…Sphinganine can be phosphorylated to sphinganine-1-phosphate or acylated to dihydroceramides. These analytes characterize the de novo sphingolipid synthesis pathway and are not generated through other means (8)(9)(10). Dihydroceramides are metabolized to ceramides that, together with sphingomyelins and complex glycosphingolipids, constitute the bulk of mammalian sphingolipids.…”
Section: Introductionmentioning
confidence: 99%